Improving Students' Speaking Ability by Using Procedural Text - Ranta Butarbutar; Angla Florensia Sauhenda (Universitas Musamus, Merauke, Papua, 2020)
Speaking English is a skill that should be having of young generation in the revolution industry 4.0 due to its uses as a communication tool in science and technology. Students’ ability in speaking can improve through various media, such as procedural text. Investigating using procedural text to improve speaking ability is the main objectives of this study. To acquire data, it used a test done in the pre-action, while observation used during the whilst-action. Finally, this action research indicated students’ improving with the speaking components; fluency, diction, intonation, sentence structure, or grammar. The study implies integrating oral and written skills can teach simultaneously. Also, combining procedural text with technology is the recommendation for future study.